2020
DOI: 10.52442/jrmi.v6i3.186
|View full text |Cite
|
Sign up to set email alerts
|

Trends in antibiotic susceptibility of enteric fever isolates among children attending a tertiary care hospital of Peshawar, KP

Abstract: Introduction: The rising trend of multi-drug resistance in bacteria has also been documented in the organism Salmonella enterica causing Typhoid or Enteric Fevers, and cases of multidrug and extended drug resistance are on the rise. Determining the trends of antibiotic susceptibility provides an important therapeutic aid to the practicing clinician.Objective: To evaluate the ten-year trends in antibiotic susceptibilities of Salmonella typhi and Salmonella paratyphi isolated from blood cultures in the paediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
4
1
Order By: Relevance
“…In addition, we are also trying to predict whether there will be sensitivity of intestinal pathogens to conventional first-line drugs reappears drug. 7 Despite the fact that there was no relation among gender overall illness incidence, our research observed that male had a greater incidence of cases (68%) than females (32%). Previous studies have indicated a somewhat different biological sex ratio which the incidence rate of male was (50.1%) and the incidence rate in female was (47.5%) (Peer et al 2021).…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…In addition, we are also trying to predict whether there will be sensitivity of intestinal pathogens to conventional first-line drugs reappears drug. 7 Despite the fact that there was no relation among gender overall illness incidence, our research observed that male had a greater incidence of cases (68%) than females (32%). Previous studies have indicated a somewhat different biological sex ratio which the incidence rate of male was (50.1%) and the incidence rate in female was (47.5%) (Peer et al 2021).…”
Section: Discussioncontrasting
confidence: 62%
“…It is primarily cause of local intestinal inflammation, diarrhea and intestinal perforation etc. 7 Upon ingestion into the body, its active replication takes place 7 to 10 days. After that they invade the epithethelial cell of the small intestine, which spread in mesenteric lymph nodes and hepatic cells through the portal vein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, state-of-the-art technologies like VITEK MS provided precision in identification, with biochemical reactions and Gram staining fortifying the characterization process. Species identification and antibiotic susceptibility were ascertained using VITEK 2 Compact (18). A comparative analysis with a study from tertiary care centers in Faisalabad and Lahore, Pakistan, further illuminated the A. baumannii landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Its temporal scope from January 2023 to July 2023 reflects a devoted effort to capture a complete view of antibiotic sensitivity patterns in typhoid fever sufferers, losing light on capacity shifts in resistance over the years. Acknowledging the severity of typhoid fever, the study's emphasis on antibiotic susceptibility is essential in guiding appropriate healing interventions (Ahmad et al, 2020;Saito et al, 2022). As underscored by the Centers for Disease Control and Prevention (CDC), the emergence of multidrug-resistant (MDR) and drastically drug-resistant (XDR) lines of Salmonella typhi poses a powerful venture to the effective management of typhoid fever (Maharjan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%